Antiques carry on - Allan, Barbara (Allan, Barbara. Trash 'n' treasures mystery, 2021)
"Vivian Borne - true-crime author, antiques dealer and ex-sheriff of Serenity, Iowa - is looking forward to meeting her new editor in London. Flying first class, rooms at the Savoy . . . Her long-suffering co-author, daughter Brandy, worries the trip will bankrupt them both, but the alternative - Mother travelling alone - is unthinkable. Brandy's almost tempted to make her fiance, Tony - Serenity's Chief of Police - call Scotland Yard and warn them Vivian's coming. But even Brandy doesn't predict their vacation will end in murder, or that she and Mother will be unceremoniously ejected from the country, with an order to leave things well alone. Vivian and Brandy need a case to write about, and Mother doesn't care which one. But as the intrepid sleuths - ably supported by doggy detective Sushi - investigate a promising local prospect, they're plunged into a complex mystery that stretches right back to London - with no choice but to carry on."--Publisher.